Exploring Analysis Teaching Materials Needs On Optimalizing Natural Science Learning - Sartika, Septi Budi; Suyidno, Suyidno; Wiguna, Akbar (JETL (Journal of Education, Teaching and Learning), 2024)
In learning, teachers must prepare teaching materials to support the implementation of learning, it is necessary to analyze the needs of teachers for teaching materials that support their routine activities. The participants were 144 natural science teachers’, using random sampling techniques. Data collection techniques using a questionnaire are distributed via google form links with WhatsApp groups. An descriptive statistics, by describing the preferences of analysis teaching materials needs on 11 statements: current natural science learning system, support for teaching materials, types of teaching materials, current natural science teaching materials, level of difficulty of materials in teaching materials, development of teaching materials, contextual teaching materials, teaching materials based on local wisdom, smartphone-based teaching materials, development of electronic modules based on local wisdom, and plans for science materials integrated with local wisdom. This research contributes to explore initial data related to teachers' needs for relevant teaching materials that can be used as a basis for developing further teaching materials.